SIGNIFIKANSI ASBÂB AN-NUZÛL DALAM PENAFSIRAN ALQUR’AN - Abdullah Karim (Jurnal Ilmiah Ilmu Ushuluddin, 2016)
The study of asbâb an-nuzûl is a part of the Qur’anic studies that discussed about events or questions directed to Rasulullah Saw. so then Qura’anic verses was gone down as the answer or the explanation of them. Based on the definition, it is not included reports or events that happened in the past before, such as Abrahah’s arrival with his troops is not asbâb an-nuzûl for Sura al-Fîl, so do the stories of Noah’s clan, ‘Ad’s, Tsamûd’s, etc. This article discusses about two matters. First, what are asbâb an-nuzûl exactly? And second, what is the significance of it to understand the meaning of Qur’anic verses? After all, there are some conclusions. Asbâb an-nuzûl talked about the reality in Qur’anic verses when they are gone down and shahîh reports must accommodate them. Asbâb an-nuzûl is very important to understand the meaning of Qur’anic verses for some reason. They will help Qur’anic reader to know the secret behind the appearance of a verse or more, to know the limit of a rule for certain verses, etc.